POTENSI HAMBAT PERMEN LUNAK SIRIH DAN PINANG TERHADAP PEMBENTUKAN BIOFILM Streptococcus mutans - Maryati Maryati; C. Hanny Wijaya; Dede R. Adawiyah; Boy M. Bachtiar (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2017)
Betle leaf (Piper betle L.) essential oil and catechu nut (Areca catechu L.) extracts have been known to be able to inhibit biofilm formation of S. mutans. This research aimed to characterize the chemical compounds of betle leaf esssential oil, screen the phytochemicals in catechu nut ethanol extract, and assess the inhibitory potential of betle and catechu in chewy candy on biofilm formation by S. mutans. The experiment included preparation of extracts and chemical characterization of the raw materials, formulation of chewy candy, measurement of biofilm inhibition, and sensory evaluation of the candy. In vitro examination for inhibitory potency of betle and catechu chewy candy against biofilm formation S. mutans ATCC 31987 was performed in adhesion phase (4 hours) and active accumulation phase (18 hours). Antibacterial assay was performed in BHI broth media on microplate 96 wells. Crystal violet 0.5% was used to stain the biofilm and Optical Density (OD) was measured at λ 450 nm. The GC-MS analysis detected 32 compounds in the essential oil of betle leaf. The Betle leaf essential oil contained chavicol acetate, isoeugenol, chavibetol acetate, chavicol, and allylcatechol 3.4-diacetate, while catechu nut ethanol extract contained flavonoids and tannins. The components were possibly the inhibitory agents of S. mutans biofilm formation. Chewy candy containing 0.8% betle leaf essential oil and 2.3% catechu nut extract had effective inhibitory potential for S. mutans biofilm formation. Inhibition during adhesion phase was 74.5±0.7%, while that for accumulation phase was 60.8±1.8%. Sensory analysis suggests that the candy was slightly liked by the panelists (5±2).